2013
DOI: 10.4236/ojemd.2013.37038
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Psychological Stress Related Cytokines (TNF Alpha, IFN-Gamma) with Essential Hypertension in Ningxia Hui Autonomous Region

Abstract: The study aimed to explore the association between psychological stress-related cytokines and essential hypertension to provide the theoretical basis for the prevention and control of the essential hypertension. We screened hypertension patients in six communities in Wuzhong City of Ningxia, and chose the healthy people who had lived in the same community for full 5 years as a control group. Finally, we selected 210 pairs of cases and controls randomly, including 108 pairs of Hui and 102 pairs of Han (50% male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…The research on IFN-γ levels with chronic diseases such as hypertension, diabetes mellitus, and dyslipidemia has also not found an increase in IFN-γ levels in comorbid conditions compared to healthy controls. Niu et al (2013) found lower IFN-γ levels in the hypertension group than in the control group [39]. Research by Nosratabadi et al (2009) found an increase in IFN-γ in patients with diabetes mellitus with nephropathy.…”
Section: Resultsmentioning
confidence: 93%
“…The research on IFN-γ levels with chronic diseases such as hypertension, diabetes mellitus, and dyslipidemia has also not found an increase in IFN-γ levels in comorbid conditions compared to healthy controls. Niu et al (2013) found lower IFN-γ levels in the hypertension group than in the control group [39]. Research by Nosratabadi et al (2009) found an increase in IFN-γ in patients with diabetes mellitus with nephropathy.…”
Section: Resultsmentioning
confidence: 93%